Effect of environmental conditions on injury rates at a Colorado ski resort. Issue 4 (19th July 2019) - Pierpoint, Lauren A; Kerr, Zachary Y; Grunwald, Gary; Khodaee, Morteza; Crume, Tessa; Comstock, R. Dawn
Abstract : Objective: To determine the effect of daily environmental conditions on skiing and snowboarding-related injury rates. Methods: Injury information was collected from a mountainside clinic at a large Colorado ski resort for the 2012/2013 through 2016/2017 seasons. Daily environmental conditions including snowfall, snow base depth, temperature, open terrain and participant visits were obtained from historical resort records. Snowpack and visibility information were obtained for the 2013/2014 through 2014/2015 seasons and included in a subanalysis. Negative binomial regression was used to estimate injury rate ratios (IRRs) and 95% CIs. Results: The overall injury rate among skiers and snowboarders was 1.37 per 1000 participant visits during 2012/2013 through 2016/2017. After adjustment for other environmental covariates, injury rates were 22% higher (IRR=1.22, 95% CI 1.14 to 1.29) on days with <2.5 compared with ≥2.5 cm of snowfall, and 14% higher on days with average temperature in the highest quartile (≥−3.1°C) compared with the lowest (<−10.6°C; IRR=1.14, 95% CI 1.03 to 1.26). Rates decreased by 8% for every 25 cm increase in snow base depth (IRR=0.92, 95% CI 0.88 to 0.95). In a subanalysis of the 2013/2014 and 2014/2015 seasons including the same covariates plus snowpack and visibility, only snowpack remained significantly associated with injury rates. Rates were 71% higher on hardpack compared with powder days (IRR=1.71, 95% CI 1.18 to 2.49) and 36% higher on packed powder compared with powder days (IRR 1.36, 95% CI 1.12 to 1.64). Conclusions: Environmental conditions, particularly snowfall and snowpack, have a significant impact on injury rates. Injury prevention efforts should consider environmental factors to decrease injury rates in skiers and snowboarders.